2022
DOI: 10.1088/1361-6668/ac4afe
|View full text |Cite
|
Sign up to set email alerts
|

DC characterization of advanced fine-filamentary MgB2 superconducting wires

Abstract: MgB2 wires with 114, 192 and 342 filaments of size 14-19 µm manufactured by HyperTech Research, Inc. have been subjected to low temperature DC measurements. R(T), I-V characteristics, critical currents and stress and strain tolerances of these wires differing by filament architecture and filament size sheathed by resistive CuNi alloys were measured and compared with the literature data. It was found that these fine-filamentary wires have high engineering current densities not reduced by twisting up to 10 mm, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In the present case, J c (6 T) is reduced by 14% for filament sizes of 83 µm and by 31% for 42 µm filaments in wires SD18 and SD 54, respectively. Figure 4(c) compares the engineering current densities (J e ) of SD18 with those of several commercial in situ made wires labelled by the abbreviation for the company and filament number described in table 3 [2][3][4][5][6]. As one can see, comparable in-field engineering current densities are measured for undoped filamentary MgB 2 wires made by different companies.…”
Section: Critical Currents and Current Densitiesmentioning
confidence: 92%
See 2 more Smart Citations
“…In the present case, J c (6 T) is reduced by 14% for filament sizes of 83 µm and by 31% for 42 µm filaments in wires SD18 and SD 54, respectively. Figure 4(c) compares the engineering current densities (J e ) of SD18 with those of several commercial in situ made wires labelled by the abbreviation for the company and filament number described in table 3 [2][3][4][5][6]. As one can see, comparable in-field engineering current densities are measured for undoped filamentary MgB 2 wires made by different companies.…”
Section: Critical Currents and Current Densitiesmentioning
confidence: 92%
“…As one can see, comparable in-field engineering current densities are measured for undoped filamentary MgB 2 wires made by different companies. The highest J e is evident for the Hitachi 10-filament wire with the largest amount of MgB 2 phase (25%) and the smallest for the fine-filament HyperTech wire, which has only 12% MgB 2 and a minimum filament size of 19 µm [6]. Recently, Kodama et al have shown that the engineering current density is roughly proportional to the superconducting fraction of MgB 2 , ranging between 20% and 35%, and filament sizes of 140-230 µm [10].…”
Section: Critical Currents and Current Densitiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Critical currents of twisted samples were measured using the standard DC technique [18] and the engineering current densities (J e ) versus the ratio of twist pitch (L t ) to wire diameter d w were plotted, see figure 2. As one can see, the J e values between 2 and 3 × 10 4 Acm −2 were measured and no J e degradation was observed for W114 and W192 up to L t /d w = 12.5.…”
Section: Examined Mgb 2 Wiresmentioning
confidence: 99%
“…It is clear that low critical current leads to low losses, but the goal for any applicable superconducting wires is to carry as high a current as possible. Therefore, another normalization takes into consideration the transport currents and AC losses normalized by the ratio of engineering current density at 20 K (see table 1) [18]. The resulting normalization is shown by figure 7(b) for all wires with the shortest twist where W342 evidently has the lowest normalized losses.…”
Section: Ac Loss Normalized By Transport Currentsmentioning
confidence: 99%